PENERAPAN TEKNIK OMBRE DIPADU CAT EYES TERHADAP HASIL KOREKSI MATA SIPIT UNTUK RIAS WAJAH MALAM HARI - ATIKA DIANA (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
This research aims to analyze the effect of the application of ombre technique combined with cat eyes on the slanted eyes shape correction in night makeup that is assessed based on indicator of the impression of the length of the eye, the impression of the width of the eye and folds of the eyelids. This research is a quantitative research with quasi experimental method with Non equevalent control group design. The object in this study were three samples with slanted eyes characteristics. Sampling using purposive sampling technique. Based on the data analysis, it was found that: a) The control group without using scote tape and fake eyelashes showed less optimal results, b) The experimental group using scote tape and false eyelashes showed very maximum results, c)The hypothesis that reads